2021
DOI: 10.1111/jocd.14675
|View full text |Cite
|
Sign up to set email alerts
|

A combined approach of subcision with either cross‐linked hyaluronic acid or threads in the treatment of atrophic acne scars

Abstract: Acne scars are a very common cutaneous problem dermatologists face in daily practice. Early treatment of acne vulgaris can minimize the incidence of scarring. 1,2 It was demonstrated that acne scars can be resulting from the interplay of multiple factors, including inflammation, degradation of the extracellular matrix, and abnormal granulation tissue formation. [3][4][5] Treatment of acne scarring continuously represents an innovative area for research. Subcision is one of the most common techniques that can g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 18 publications
3
10
0
Order By: Relevance
“…Our study showed that HA filler was superior to saline, therefore based on this previously mentioned study, it can be inferred that is likely superior to subcision. A more recent study showed subcision with HA filler was superior to subcision with threads or subcision alone (improvements in 94.1%, 82.4%, and 67.3% of patients, respectively) 48 . In our study, HA filler alone yielded a similar result in patient‐rated improvement (93%) as the subcision with HA filler arm of that study 48 signifying that subcision may not be necessary.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Our study showed that HA filler was superior to saline, therefore based on this previously mentioned study, it can be inferred that is likely superior to subcision. A more recent study showed subcision with HA filler was superior to subcision with threads or subcision alone (improvements in 94.1%, 82.4%, and 67.3% of patients, respectively) 48 . In our study, HA filler alone yielded a similar result in patient‐rated improvement (93%) as the subcision with HA filler arm of that study 48 signifying that subcision may not be necessary.…”
Section: Discussionsupporting
confidence: 78%
“…A more recent study showed subcision with HA filler was superior to subcision with threads or subcision alone (improvements in 94.1%, 82.4%, and 67.3% of patients, respectively) 48 . In our study, HA filler alone yielded a similar result in patient‐rated improvement (93%) as the subcision with HA filler arm of that study 48 signifying that subcision may not be necessary. Therefore, we believe HA filler should be used as a first‐line stand‐alone treatment for distensible atrophic rolling scars.…”
Section: Discussionsupporting
confidence: 78%
“…Our findings outperformed those of a previous study that used microfat after subcision to treat severe atrophic acne scars and avert the reconnection of fibrous bonds 43 . Furthermore, using hybrid H‐HA/L‐HA after subcision produced better results than using HA or threads after subcision, and with fewer sessions 44 . In severe atrophic acne scarring, TSASRT outperforms platelet‐rich plasma as an adjunctive therapy to a combined subcision and needling treatment 45 .…”
Section: Discussionsupporting
confidence: 59%
“…In severe atrophic acne scarring, TSASRT outperforms platelet‐rich plasma as an adjunctive therapy to a combined subcision and needling treatment 45 . When compared to other studies, this study yielded excellent results, fewer sessions, a simple technique, and higher patient satisfaction 43–45 …”
Section: Discussionmentioning
confidence: 75%
“…Forty men and women took part in this study based on 3 sessions conducted at 1-month intervals. Subcision combined with hyaluronic acid or threads gave better clinical improvement than subcision alone [ 63 ].…”
Section: Methods Of Acne Scars Managementmentioning
confidence: 99%